Preparation and photocatalytic properties of Cu2ZnSnS4 for H2 production. (30th September 2020) - Wang, Jiansheng; Zeng, Xiongfeng; Zhao, Yingna; Zhang, Wenli
Abstract: Cu2 ZnSnS4 (CZTS) thin film photocatalytic water splitting for hydrogen production under visible light irradiation has been reported together with CZTS nanoparticles prepared by ultrasonic spray pyrolysis and hydrothermal method, respectively. CZTS thin film provided higher H2 production rate (68.68 μ mol · g −1  · h −1 ), which was 32 times higher than that of CZTS nanoparticles (2.08 μ mol · g −1  · h −1 ) without loading any noble metals. What's more, photocatalytic activity of CZTS thin film remained 94% after 48 h which confirmed the good stability and reusability of CZTS thin film. CZTS thin film is a potential and durable candidate for photocatalysis.